An energy-efficiency technique for n-way stream joins in wireless sensor networks - Boubekeur DJAIL; Walid Khaled HIDOUCI; Malik LOUDINI (Revue Nature et Technologie, 2023)
In wireless sensor networks, the critical factor is the sensors energy. The exhaustion of this energy causes network paralysis. In wireless sensor networks, the join operation needs a lot of energy consumption. This energy is so very high for nway join queries, and more very high for nway stream queries. Little work has been done to address this problem. We present in this paper, an energy-efficiency technique for n-way joins execution between data streams in wireless sensor networks. The experiment conducted has shown good performance of the proposed technique compared to SENS-join technique.